Comparative study of actinic keratosis treatment with 3% diclofenac sodium and 5% 5-fluorouracil - Majorie Mergen Segatto; Sergio Ivan Torres Dornelles; Vera Bauer Silveira; Gabriela de Oliveira Frantz (Sociedade Brasileira de Dermatologia, 2013)
BACKGROUND: Actinic keratosis is a frequent lesion which occurs in sunlight exposed areas. Diclofenac sodium and 5-Fluorouracil are effective, non-invasive and easy-to-apply topical treatment options. OBJECTIVES: To assess and compare the effectiveness of 3% diclofenac sodium associated with 2.5% hyaluronic acid and of 5% 5-Fluorouracil for the treatment of actinic keratosis, as well as the patient's degree of satisfaction and tolerability. METHODS: 28 patients with a clinical diagnosis of actinic keratosis were randomized to receive diclofenac sodium or 5-Fluorouracil and were clinically assessed before and after treatment as well as 8 weeks after the end of treatment. Modified versions of the Investigator and Patient Global Improvement Scores were used. RESULTS: The average number of lesions in the diclofenac sodium group before and after treatment was 13.6 and 6.6 (p<0,001), respectively, while it was 17.4 and 3.15 (p<0.001) in the 5-Fluorouracil group. There was a significant reduction in the number of lesions in the 5-Fluorouracil group in relation to the diclofenac sodium group (p<0.001). To the non-blinded physician, there was a higher satisfactory therapeutic response in the 5-Fluorouracil group (p<0.001); to the blinded physician, there was a higher satisfactory response in this same group, although not statistically significant (p=0.09). There was a high degree of satisfaction in both groups (73% in the diclofenac sodium group and 77% in the 5-Fluorouracil group; p=0.827). Regarding adverse effects, the diclofenac sodium group presented a higher degree of satisfaction (93.3% vs 38.4%; p=0.008). Erythema, edema, crusts and itching were significantly higher in the 5-Fluorouracil group. CONCLUSION: We concluded that 5-Fluorouracil was more effective; however, it showed lower tolerability than diclofenac sodium.